Really very crunchy : a beginner's guide to removing toxins from your life without adding them to your personality - Morrow, Emily, 1988- (Zondervan Books, 2024)
"Social media star Emily Morrow invites readers into a practical, accessible--and funny--journey toward a healthier lifestyle in Really Very Crunchy. Emily shows you how crunchy is really a spectrum, and anyone can take steps to improve their quality of life through being a little bit crunchy ... or even Really Very Crunchy, if you please"--